COMPARATIVE ANALYSIS OF SOFTWARE DEVELOPMENT SYSTEMS BASED ON FRAMEWORKS - PAZDRIY, Ihor (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article provides a comparative analysis of web frameworks based on the Python programming language. The right choice of a software development tool will allow developers to speed up the process of designing and software implementation of web resources. With the development of programming languages, solutions have begun to appear that make it easier for programmers to create web applications. In recent years, many tools of this type have been developed, including web frameworks. Some of them are used to develop small web applications, and other frameworks are used to create large-scale systems. The existing web frameworks differ from each other, but choosing them can be a difficult task for a programmer. Therefore, it is necessary to specify several parameters that are common to frameworks, according to which the desired web framework should be selected. The selected criteria make it possible to evaluate the frameworks more qualitatively and more objectively and speed up the process of design and software implementation of web resources. Due to the high demand for web applications, developers need to develop cost-effective, secure and well-coded web applications. Analyzing the Django framework, it can be argued that it is the most popular for web development, written in the Python programming language and using the MVC architecture. It is ideal for application projects with limited time and a small budget. If the application is not very voluminous and only simple URL routing and templates with a simple context are needed, then the Flask framework can be used instead of Django. The framework for building a Flask application in the resulting HTML files contains additional tags and scripts. The mechanism of work of processing forms also works differently. Flask stores more information about form fields on pages. The size of HTML files created using the Flask framework turns out to be significantly larger.